Bio-therapeutics effects of probiotic strain on the gastrointestinal health of severely acute malnourished children - Rehman, Habib-Ur-; Nasir, Muhammad; Abdul Jabbar, Makhdoom; Ayaz, Muhammad; Ali, Muhammad Asif; Imran, Muhammad; Gondal, Tanweer Aslam; Tufail, Tabussam; Aslam, Farhan; Qaisrani, Tahira Batool; Sattar, Muhammad Umair; Salehi, Bahare; et al. (Cellular and Molecular Biology, 2020)
The core objective was to evaluate the effect of probiotic fortification at three phases of formula milk administration in malnourished children. A dose related effect was determined in 30 severely acute malnourished children (6-59 months) in a double-blind, randomized design. According to the results, serum albumin levels, treatment T2 (6 billion cfu) has significantly increased albumin levels (3.7g/dL) and the effect of phase-III (Plumpy'nut) was found to be better. Results regarding sodium levels showing probiotic-dose have significant effect (Pâ‰¤0.05) in phases as well. Moreover, the effect of T1 i.e. 3 billion cfu of probiotics has significantly reduced sodium levels (141.8mmol/L) vs. others and the effect of phase-II was better on reducing sodium levels. which is further confirmed in terms of reduced erythrocyte sedimentation rate levels at phase-III (29.566 vs. phase-II, 41.3 and phase-I, 46.533 mm/h). Conclusively, the effect of 6 billion cfu at phase-III was more effective on blood parameters.